An informative search of dyes content rhodamin b in blusher, lipstick, and eyeshadow cosmetics - Haryati, Husnul; Guntarti, Any (Journal of Halal Science and Research, 2022)
Decorative cosmetics are preparations used to beautify the appearance and cover up flaws in the skin, such as blemishes on the skin so that the user looks fresher. Examples of decorative cosmetics include lipstick, blusher, eye shadow, and so on, which are usually given the addition of synthetic dyes such as rhodamine. The addition of rhodamine B dye to cosmetics is not permitted. However, the use of dyes is still widely abused by irresponsible people. This review article aims to see whether Rhodamine B dye is present in decorative cosmetics such as blusher, lipstick, and eye shadow. I am writing review articles by searching using search engine assistance, namely Google Scholar, PubMed, and Science Direct. A literature search was performed using the following keywords or terms and strategies: "analysis" OR "determination" OR "Rhodamine B" AND "cosmetics" AND "lipstick" OR "blush" OR "eye shadow.” Data used in the review of this article refers to studies or studies that have been carried out previously, namely in the form of articles or journals for the last five years, from 2015 to 2019, and other sources such as textbooks and these data. The results obtained in the search for articles were from 125 journals. They are then selected based on predetermined inclusion criteria. Seven journals fall into the inclusion criteria. The sample criteria include registered BPOM, not registered with BPOM, red and inexpensive color. The search results concluded that there are still many rhodamine B coloring agents in decorative cosmetics circulating in Indonesia, such as blush, lipstick, and eye shadow. Dede Komarudin did the highest levels of Rhodamine B in Siva Fauziah, Ratih Pramintari (2019) with a blush on a 776.98 μg/mg sample taken from Jatinegara Market, Jakarta.